2017
DOI: 10.1111/maps.12845
|View full text |Cite
|
Sign up to set email alerts
|

Revising the shock classification of meteorites

Abstract: The current shock classification scheme of meteorites assigns shock levels of S1 (unshocked) to S6 (very strongly shocked) using shock effects in rock-forming minerals such as olivine and plagioclase. The S6 stage (55-90 GPa; 850-1750°C) relies solely on localized effects in or near melt zones, the recrystallization of olivine, or the presence of mafic high-pressure phases such as ringwoodite. However, high whole rock temperatures and the presence of high-pressure phases that are unstable at those temperatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
158
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(174 citation statements)
references
References 89 publications
(134 reference statements)
16
158
0
Order By: Relevance
“…However, the formation mechanism of maskelynite is still a matter of debate. Many researchers hold that maskelynite is a diaplectic plagioclase glass formed via solid-state transformation [3,[40][41][42][43]. However, Chen et al [44] and El Goresy et al [45] suggested that maskelynite could be formed by melting of plagioclase and is a dense quenched glass.…”
Section: Shock Pressure and Temperature Of The Shock Veinmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the formation mechanism of maskelynite is still a matter of debate. Many researchers hold that maskelynite is a diaplectic plagioclase glass formed via solid-state transformation [3,[40][41][42][43]. However, Chen et al [44] and El Goresy et al [45] suggested that maskelynite could be formed by melting of plagioclase and is a dense quenched glass.…”
Section: Shock Pressure and Temperature Of The Shock Veinmentioning
confidence: 99%
“…According to the latest shock classifications of meteorites by Fritz et al [3], the occurrence of maskelynite and ringwoodite in local melt zones of meteorites needs a shock pressure >15 GPa. But this shock classification can't provide the precision formation pressure of maskelynite.…”
Section: Shock Pressure and Temperature Of The Shock Veinmentioning
confidence: 99%
See 3 more Smart Citations